The prevalence of cardiovascular disease risk factors among students of International Islamic University Malaysia, Kuantan Campus - Abdul Shomad, Mukramah; A. Rahman, Nor Azlina; A.Rahman, Nor Iza; Haque, Mainul (Journal of Applied Pharmaceutical Science (JAPS), 2016)
Cardiovascular disease (CVD) has become the leading cause of death among the non-communicable diseases worldwide. There are many contributing risk factors for the emergence of CVD. A cross-sectional study was conducted to observe the prevalence of CVD risk factors among International Islamic University Malaysia (IIUM) Kuantan Campus (KC) students. 156 participants from different faculties and years of study participated; among them 56 participants were able to complete the whole procedures. A set of questionnaires were distributed to participants. Anthropometric measurements, weight, height, waist circumference, random blood glucose (RBG) and blood pressure were measured. Prevalence of hypertension was 4%. The mean systolic blood pressure (SBP) and diastolic blood pressure (DBP) was 114.268 ± 12.034 and 74.964 ± 8.636 of mmHg respectively. Prevalence of overweight and obesity was 34%, with women having a higher percentage (21%) than men (12%). The mean Body-Mass Index (BMI) was 22.184 ± 4.435 kg/m2. The waist circumference has an average of 71.661 ± 9.215 cm. Prevalence of high blood glucose was absent, and the mean blood glucose level was 6.007 ± 1.018 mmol/L. Dietary fibre-rich foods; vegetables were eaten 6-7 times per week, granola bars and fruits were eaten 1- 2 times per week. Home cooked foods were taken 1-2 times per week. Fast foods were taken frequently around 3- 5 times per week. The study community was engaged in physical activities such as brisk-walk, skipping and sports. Smoking prevalence was 4% only among the male population. The stress level was moderate. The students of IIUM KC practiced healthy diet and were physically active. The CVD-related risks do not prevail among the IIUM KC population.